An Analysis of Grammatical Use on Second Language Acquisition of Thailand Student - Minkhatunnakhriyah Minkhatunnakhriyah; Albiansyah Albiansyah; Fahriany Fahriany (Universitas Teknokrat Indonesia, 2022)
Second language acquisition refers to the study of how students learn a second language in addition to their first language. Furthermore, L2 learners and also L1 learners need to understand a linguistic system that makes it possible to understand when speaking second languages. The grammatical structure of language is needed in order to get the context of what would be uttered. The purpose of this research is to find out the types of grammatical use in twenty-five years old student university from Thailand and the process of acquiring English grammar procedure. This research was Qualitative descriptive. To collect the data of this research through interviewing and recording participants by ten questions. After getting the data the researchers, transcript the result of Thailand student interview to analyze types of grammatical use and process of acquiring English grammar procedure by adopted theory from Tarigan (1990) in his book pengajaran pemerolehan Bahasa. The result of this research shows that there were 18 types of grammatical used in Thailand's student speaking, that 5 of the simple present, 2 degrees of comparison, 2 Noun phrase use, 3 Auxiliary verbs, and 6 used of simple past. Meanwhile, related to the process of acquiring a second language based on the resulting interview of a Thailand student. The process of acquiring a second language through reading some English novels, listening to the music of English songs, and memorizing vocabularies. Although there was interference language that influences Thailand's student speaking, It will inevitably occur in any situation where someone has not mastered a second language.